KARAKTERISASI DAN SKRINING FITOKIMIA SIMPLISIA DAUN SELUTUI PUKA (Tabernaemontana macracarpa Jack) - Fitri Handayani; Anita Apriliana; Hellen Natalia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Selutui puka (Tabernaemontana macrocarpa Jack) is a plant that is efficacious for treating tumor diseases and blisters. Simplicia is said to be of high quality if it meets the simplicia requirements. The initial process to find out the quality of simplicia is characterization. The study aims to determine the specific, non-specific characteristics and content of chemical compounds.This research is non experimental. The research starts from sampling, determination, making simplicia, characterization which includes macroscopic test, microscopic test, determination of moisture content, soluble ethanol extract content, water soluble extract content, moisture content, ash content, acid insoluble ash content and phytochemical screening. Data were analyzed using descriptive methods.Specific characteristics in the macroscopic and organoleptic tests showed long round leaves, pinnate leaf bones, spiky rounded leaf tips, rounded base of leaves, flat leaf edges, thick leaf flesh, dark green color, leaf width of 4.5 cm long, 12.5 cm long. The powder is dark green, aromatic and has a bitter taste. Microscopic tests include cover hair, vessels, bundles of stairs, upper epidermis and lower epidermis with bidiastic type stomata, 12% soluble ethanol, 15% water soluble extract. Non-specific characteristics consisted of 8% moisture content, 6.51% ash content, acid insoluble ash content 0.246%. The results of phytochemical screening contain alkoloid, flavonoids, tannins, saponins and steroids.